2018
DOI: 10.21608/ajfm.2018.15879
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brown Heroin and Tramadol Dependency on Reproductive Axis in Adult Male Albino Rats

Abstract: Objective: Drugs addiction is considered a general major problem all over the world causing massive detrimental effects for the addict, communities and governments. The study was designed to assess the dependency impact of concurrent brown heroin and Tramadol administration on reproduction in rats. Material and methods: Sixty adult male albino rats were divided into untreated control (I), vehicles groups citric acid (II), saline (III), brown heroin (IV), tramadol (V) and concurrent brown heroin and tramadol (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Histopathological analysis of the testis supports the biochemical and molecular fi ndings. We found severe irregular changes in the testicular tissues of Tra groups, compared to the control group; these fi ndings are in line with previous studies (4,62,63). In general, the present fi ndings support Tra-induced toxicity in the testicular tissue.…”
supporting
confidence: 93%
“…Histopathological analysis of the testis supports the biochemical and molecular fi ndings. We found severe irregular changes in the testicular tissues of Tra groups, compared to the control group; these fi ndings are in line with previous studies (4,62,63). In general, the present fi ndings support Tra-induced toxicity in the testicular tissue.…”
supporting
confidence: 93%
“…In a modest-sized postmortem study of perivascular changes, the neurovascular effects of heroin abuse were examined, revealing a higher incidence of inflammatory cells, edema, and hemorrhaging in the perivascular area [46]. Studies have also reported an increased burden of EPVS in both humans and animals who use drugs [47,48], supporting the hypothesis that long-term heroin abuse disrupts BBB permeability, causes inflammation, and increases EPVS, all leading to elevated brain glymphatic-system function. The glymphatic function comprises three different parts: the cerebrospinal-fluid (CSF) influx along the periarterial space, CSF-ISF exchange, and ISF efflux along the perivenous space [49].…”
Section: Discussionmentioning
confidence: 99%